SENSITIVITY OF DRAINAGE MORPHOMETRY AND TOPOGRAPHIC ATTRIBUTES TO THE SOURCE AND SPATIAL RESOLUTION OF DSM AND DEM - Capoane, Viviane (2022)
The determination of stream channel and terrain attributes is dependent on the spatial resolution of Digital Surface Models (MDS) and Elevation (DEM) and the source of the altimetric data used. In this work, the sensitivity of drainage morphometry and terrain attributes of an urban-rural watershed to the spatial resolution and source of MDS and MDE was analyzed. Five MDSs obtained via orbital remote sensing (radar), with spatial resolutions of 12.5, 30 and 90 m, and one MDE of 5 m generated with altimetric data obtained via terrestrial remote sensing (aerial photographs) were used. The stream network extracted from DEM 5 allowed a more precise and accurate delineation than that of the MDS for places where the contribution area was larger. There were incongruities in the drainage headwaters for all topographic bases, which is attributed to the flow distribution algorithm used. In the low spatial resolution MDS (Alos Palsar, SRTM 30, 90, Topodata and Aster) the topographical features were not represented realistically. The terrain attributes derived from the high spatial resolution DEM realistically represented the topographic characteristics of the watershed, including anthropogenic landforms.